2006
DOI: 10.1116/1.2207148
|View full text |Cite
|
Sign up to set email alerts
|

Understanding ion-milling damage in Hg1−xCdxTe epilayers

Abstract: Transmission electron microscopy (TEM) is widely used for the characterization of the microstructure of Hg1−xCdxTe epilayers. Traditional TEM sample preparation methods, which usually involve argon ion milling, can easily cause damage to the material, and the size and density of the induced defects depend on the milling conditions. In this work, the structural damage caused by argon ion milling of Hg1−xCdxTe epilayers has been investigated. Multilayer samples with different Hg concentrations, as grown by molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…The TEM measurements have been discussed in detail elsewhere, 10,[22][23][24][25] including the additional steps required to reduce ion-milling damage and preparation artefacts. 25 …”
Section: Methodsmentioning
confidence: 99%
“…The TEM measurements have been discussed in detail elsewhere, 10,[22][23][24][25] including the additional steps required to reduce ion-milling damage and preparation artefacts. 25 …”
Section: Methodsmentioning
confidence: 99%
“…The mechanical polishing and dimpling typically reduced the sample thicknesses to 10$12 lm, and small holes in the films were then made by ion-milling at low energy (2.5$3 keV), using a liquid-nitrogen-temperature cooling stage to minimize any thermal or ion-beam damage. 27 The TEM characterization studies were mostly carried out using a JEM-4000EX high-resolution electron microscope operated at 400 keV and with a structural resolution of $1.7 Å . All samples were prepared for observation along {110}-type zone-axis projections so that the direction of the electron beam would be aligned perpendicular to the growth surface normal.…”
Section: Methodsmentioning
confidence: 99%
“…These observations were made before we fully appreciated the importance of ensuring that the sample was really at liquid-nitrogen temperature during ion milling. 6 It was found that the p-type layer was generally of high quality. Small defects were, however, visible in the region of the p-n junction and in both n and p layers, although the density of defects in the p-type layer was much lower.…”
Section: Resultsmentioning
confidence: 98%